2002
DOI: 10.1210/jcem.87.5.8460
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short-Term Administration of Two Low DosesVersusthe Standard GH Replacement Dose on Insulin Sensitivity and Fasting Glucose Levels in Young Healthy Adults

Abstract: GH has both diabetogenic and insulin-like actions. Supraphysiological GH doses are known to reduce insulin sensitivity (S(I)), but lower doses are less well studied. We therefore compared the effects of two physiological GH doses (intermediate, 0.0033 mg/kg x d; low, 0.0017 mg/kg x d) with the standard adult GH deficiency replacement dose (standard, 0.008 mg/kg x d) on S(I), beta-cell function, IGF-I, and IGF binding proteins (IGFBPs)-1 and -3 in healthy adults. Eleven healthy nonobese volunteers (4 males and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Of note is that many of the earlier studies assessing the effects of GHRT on glucose metabolism and insulin sensitivity used weightbased GH dosing, whereas current practice is to use an individualized dosing with lower starting doses, resulting in much less frequent side effects (36). Furthermore, it has been demonstrated that lower starting doses of GH may improve insulin sensitivity in healthy subjects, notably in males, in contrast to the earlier standards using higher doses which induced insulin resistance (37). In our cohort, the incidence of T2DM was not increased in patients receiving long-term GHRT but was increased for patients without such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that many of the earlier studies assessing the effects of GHRT on glucose metabolism and insulin sensitivity used weightbased GH dosing, whereas current practice is to use an individualized dosing with lower starting doses, resulting in much less frequent side effects (36). Furthermore, it has been demonstrated that lower starting doses of GH may improve insulin sensitivity in healthy subjects, notably in males, in contrast to the earlier standards using higher doses which induced insulin resistance (37). In our cohort, the incidence of T2DM was not increased in patients receiving long-term GHRT but was increased for patients without such treatment.…”
Section: Discussionmentioning
confidence: 99%